Markers of muscle damage and performance recovery after exercise in the heat - Nybo, L.; Girard, O.; Mohr, M.; Knez, W.; Voss, S.; Racinais, S. (Medicine & Science in Sports & Exercise, 2013)
Purpose: This study aimed to determine whether competitive intermittent exercise in the heat affects recovery, aggravates markers of muscle fiber damage, and delays the recovery of performance and muscle glycogen stores.